THE PROBLEM LEARNING OF HOSTORY OF ISLAM CULTURE (SKI) IN MADRASAH ALIYAH IN BINJAI - Siti Nasuha, Hasan Asari, Syaukani (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
The research aims to find out the learning problems of history of Indoesian Culture inthe Islamic School in Binjai City. The problem includes: (1) curriculum (2) teaching staff (3)learning strategies and (4) aspects of learning resources. This study uses a qualitative approach.The study was conducted on four Islamic schools in Binjai consisting of one (1) state highschool and three (3) private high of Islamic schools. The data sources of this study are data,and documents. The research data was collected through observation, interviews, and documentanalysis and using data reduction techniques, data presentation and conclusion drawing inthe school environment and in the classroom. The research subjects consisted of students andteachers. The object of research is the learning problems of the SKI. The research instrumentsare interview guides, observation sheets, and field notes. The data is analyzed by qualitativedescriptive method. Based on this qualitative descriptive analysis, some conclusions can befound are:First, SKI learning problems of the curriculum aspects, are: (1) planning and implementationof learning has not been fully implemented properly, (2) curriculum; the subject matter is stilltoo much (extensive discussion), (3) time allocation of learning is too short, (4) administrationduties of teacher are too much. Second; SKI learning problems from the aspect of teachingstaff include: (1) Qualifications, competencies, and SKI teacher certification are inadequate,(2) Teachers teach more than one lesson and some of them teach non-cognate subject areas(3) Teacher’s experience teaching is not professional, (4) MGMP; The Subject Teacher Conferencewhich was formed in November 2018 ago, has not yet proceeded in accordance with thefunctions and objectives of the MGMP in Madrasah Aliyah Binjai. Third; SKI learning problemsfrom aspects of learning strategies include: (1) The learning methods are still conventional, (2)Less creative learning, (3) SKI lessons are considered less important, (4) Learning at the end ofthe lesson time table, (5) Differences in student education background. Fourth; SKI learningproblems from aspects of learning resources include (1) The use of audio-visual media as SKIconcrete learning and (2) Limitations of textbooks, learning support books and other teachingaids, especially in Private Madrasah Aliyah.Keywords: Learning Problems, Islamic Culture History, Islamic Senior High School